PENILAIAN PROBABILITAS HUMAN ERROR DI INDUSTRI TAMBANG BATUBARA - Ratna Ayu Ratriwardhani; Friska Ayu (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Based on data from the Health and Safety Executive, it can be concluded that as many as 90% of accidents are caused by human error. Coal mining is an industry that has a high risk of work accidents. If the mining process is not following procedures, then lives will be at stake. Human error probability assessment needs to be done because most accidents that occur in coal mining are caused by human error. HRA (Human Reliability Analysis) is part of the risk assessment process which aims to calculate the HEP value. HRA has been used in many studies to assess the risks involved in large, complex, and dangerous systems. The Success Likelihood Index Method (SLIM) is a method of analysis for human reliability. Prevention and control of human error need to be done at every stage of work. SLIM can analyze HEP at each stage of the work. SLIM aims to obtain a HEP value. To get the HEP value, we must first find the SLI (Success Likelihood Index) value. Finding the SLI value comes from a weighting questionnaire and PSF (Performance Shaping Factor) assessment that has been filled in by an expert judgment. After the HEP value is obtained, it can be seen which jobs fall into the safe risk level and which the risk cannot be accepted. Furthermore, risk reduction is carried out by making a task analysis of jobs that have a high hazard risk. Based on the research results, it can be seen the factors that cause a human error, namely unsafe conditions, unsafe actions, personal factors, and job factors. While the task that has the highest HEP value is on task 4, which is equal to 0,006932. The task with the smallest HEP value is task 1, amounting to 0,006478.